Selective Chemical Upcycling of Mixed Plastics Guided by a Thermally Stable Organocatalyst. (11th February 2021) - Jehanno, Coralie; Demarteau, Jeremy; Mantione, Daniele; Arno, Maria C.; Ruipérez, Fernando; Hedrick, James L.; Dove, Andrew P.; Sardon, Haritz
Abstract: Chemical recycling of plastic waste represents a greener alternative to landfill and incineration, and potentially offers a solution to the environmental consequences of increased plastic waste. Most plastics that are widely used today are designed for durability, hence currently available depolymerisation methods typically require harsh conditions and when applied to blended and mixed plastic feeds generate a mixture of products. Herein, we demonstrate that the energetic differences for the glycolysis of BPA‐PC and PET in the presence of a protic ionic salt TBD:MSA catalyst enables the selective and sequential depolymerisation of these two commonly employed polymers. Employing the same procedure, functionalised cyclic carbonates can be obtained from both mixed plastic wastes and industrial polymer blend. This methodology demonstrates that the concept of catalytic depolymerisation offers great potential for selective polymer recycling and also presents plastic waste as a "greener" alternative feedstock for the synthesis of high added value molecules. Abstract : The energetic differences for the glycolysis of BPA‐PC and PET in the presence of a protic ionic salt TBD:MSA catalyst enable the selective and sequential depolymerisation of these two commonly employed polymers. Functionalised cyclic carbonates can be obtained from both mixed plastic wastes and industrial polymer blend.